5:2 intermittent fasting tapers food intake in the refeeding state and ameliorates metabolic disturbances in mice exposed to olanzapine - Zhang, Chengfang; Li, Han; Yan, Yabin; Zhang, Xiyan; Tu, Zhilan (Frontiers in Psychiatry, 2022)
A considerable number of patients suffer from adverse metabolic reactions caused by atypical antipsychotics (AAPs), however, current management strategies are disappointing to clinicians. Preclinical studies have consistently demonstrated that intermittent fasting (IF) has robust disease-modifying efficacy in animal models in a wide range of pathological conditions, especially obesity and diabetes. However, it is unclear what role IF can play in addressing AAPs-induced metabolic disturbances. In our study, we found that a 5:2 IF regimen significantly ameliorated the metabolic disturbances induced by olanzapine (a drug representative of AAPs) in animal models. Meanwhile, our research suggests that IF altering food intake during the refeeding phase may account for the metabolic benefit. This study provides supporting evidence regarding a potentially cost-effective intervention strategy for AAPs-induced metabolic disturbances.